DINAMIKA PEMBUATAN PERATURAN DAERAH TENTANG WAJIB BELAJAR MADRASAH DINIYAH TAKMILIYAH AWALIYAH DI KOTA MEDAN - Indra Fauzan; Zakaria Taher (Program Studi PPKn FIS UNJ & Asosiasi Profesi PPKn Indonesia, 2016)
ABSTRACT This study is focused to the making process of local regulations on compulsory education Takmilihan Awaliyah Madrasah Diniyah. As for the reason researchers reviewing this research due to the Change of religious-based Perda is first of all that there is in the city of Medan. In the process of its compilation will certainly undergo Dynamics refers to the context of the city of Medan that heterogeneity. As for the research methods used in this study using qualitative method through a descriptive approach, so that research results can eventually be clearly reflected the problems that arise from the creation of the religion-based Change. Results from the study found that there is little the dynamics in the endorsement on the plenary meeting of the MDTA Perda Kota Medan initially some faction representative in Medan city requesting that a deeper discussion done against Perda MDTA, because it is related to the spirit of promoting diversity that exists in the city of Medan. Keywords: Perda MDTA, diversity, compulsory education, legislative.